X-ray spectra of circumgalactic medium around star-forming galaxies: connecting simulations to observations. Issue 1 (26th November 2021) - Vijayan, Aditi; Li, Miao
ABSTRACT: The hot component of the circumgalactic medium (CGM) around star-forming galaxies is detected as diffuse X-ray emission. The X-ray spectra from the CGM depend on the temperature and metallicity of the emitting plasma, providing important information about the feeding and feedback of the galaxy. The observed spectra are commonly fitted using simple one-temperature (1-T) or two-temperature (2-T) models. However, the actual temperature distribution of the gas can be complex because of the interaction between galactic outflows and halo gas. Here, we demonstrate this by analysing 3D hydrodynamical simulations of the CGM with a realistic outflow model. We investigate the physical properties of the simulated hot CGM, which shows a broad distribution in density, temperature, and metallicity. By constructing and fitting the simulated spectra, we show that, while the 1-T and 2-T models are able to fit the synthesized spectra reasonably well, the inferred temperature(s) does not bear much physical meaning. Instead, we propose a lognormal distribution as a more physical model. The lognormal model better fits the simulated spectra while reproducing the gas temperature distribution. We also show that when the star formation rate is high, the spectra inside the biconical outflows are distinct from those outside, as outflows are generally hotter and more metal enriched. Finally, we produce mock spectra for future missions with the eV-level spectral resolution, such as Athena,   Lynx, the Hot Universe Baryon Surveyor, and the X-ray Imaging and Spectroscopy Mission .